Diabetic Foot Ulcers Treated with Nanotherapy: A Short Communication - Lopez-Goerne, Tessy; Valienet, Rafael; Gonzalez-Bondani, Antonella; Padilla-Godínez, Francisco J. (British Journal of Healthcare and Medical Research, 2024)
The current study proposes an innovative approach: the development of a nanotherapeutic particles designed to encompass all the desired functionalities outlined by previous researchers. These include: a) bactericidal properties, b) the ability to generate ROS species from lactic acid when the Krebs cycle deviates to the Cori cycle, c) promotion of angiogenesis and oxygenation of wounds, and d) acting as a catalyst for cell regeneration, thereby facilitating the closure of diabetic foot ulcers. These nanotherapeutic particles are synthesized from an organometallic compound integrated into a polymeric amorphous matrix. Crucially, it is superficially coated with a variety of functional groups, exhibiting a particle size ranging from 1 to 5 nanometers as determined by transmission electron microscopy (TEM), with a specific surface area exceeding 700 m2/g. Preliminary preclinical findings have been documented, and we present additional promising outcomes in this report.